Using authentic picture books and illustrated books to improve L2 writing among 11-year-olds. Issue 1 (2nd January 2017) - Birketveit, Anna; Rimmereide, Hege Emma
Abstract : The case study investigates what impact extensive reading of authentic picture books/illustrated books had on the learners' writing skills in a Norwegian EFL (English as a foreign language) classroom of 11-year-olds. Furthermore, the study also looks into the importance the pictures/illustrations had for the learners and what type of picture–text interaction they favoured. The case study was designed to allow the learners the freedom to choose for themselves, from a list provided, which books to read. The learners were asked to read as many books as possible from a selection of 70 picture books/illustrated books, though a minimum of three, in the course of four weeks. Both qualitative and quantitative methods and procedures were employed through log books, a questionnaire, individual interviews and learners' written texts before and after the reading project. The study reveals that the project improved learners' motivation to read and led to improvement in their writing skills. It raises questions about the current practice of heavy reliance on course books, but further research is needed to support the findings.